Wages and employment in a unionized economy: Practical implications of theoretical considerations in the context of Finland - Timo Tyrväinen (Bank of Finland, 1988)
This article evaluates the fundamental characteristics of Finnish labour markets. As the unionization rate in Finland is exceptionally high by international standards, a bargaining approach incorporating the unions' key role in wage setting is applied. An analysis is made of basic trends in those factors which theoretical considerations imply as being relevant. The "wedge" between product wages and after tax consumption wages is evaluated with special care. It is stated that the wedge cannot be claimed to be a key factor contributing to the unfavourable trends seen in Finnish labour markets since the late 1970s. It is also argued that collective incomes policy measures have contributed to shortening of the adjustment lags in labour markets at least in some relevant occasions.
URN:NBN:fi:bof-201908051327
Keywords: 330